O Percurso Editorial da obra Vida de la Sereníssima Infanta Doña Maria de Frei Miguel Pacheco - Vera Peixoto (Universidade do Porto, 2010)
The book Vida de la Serenissima Infanta D. Maria, by Friar Miguel Pacheco (? – 1668) of the Order of Christ, was published in 1675, in Lisbon. Its subject matter is, as the title indicates, Princess Maria (1521 – 1577), daughter of King Manuel I of Portugal (1469 – 1521). The book is inscribed in the long tradition of life-writing, and it intends to offer a royal/real-life example of virtue and devotion to its readers/listeners. Although the text was published in Lisbon in 1675 (only known edition), it was written in Madrid. Friar Miguel Pacheco had been sent there by his Religious Order, with the task of carrying out the legacies of Princess Maria, as displayed in her testament. Thus, the printing of the book was started in the Castilian court, only to be interrupted in 1668, when the author passed away, and resumed eight years later in Portugal. In this article we intend to explore the exceptional and obscure editorial route this book undertook, between 1668 and 1675, between Madrid and Lisbon. We will base our analysis, to a great extent, in an incomplete printed copy recently found in the Castilla-La Mancha Library, in Toledo, and the observation of the variants it presents.